SOCIOLOGICAL ASPECTS OF THE USE OF MODERN DENTAL IMPLANTS WHEN PLANNING FIXED PROSTHETICS. - Tashpulatova Kamilla Maratovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The paper examines the sociological aspects of dental implantation. A sociological a survey of doctors from dental organizations, on the basis of which a modern description of clinical, organizational And economic problems V orthopedic treatment absence teeth With using artificial supports